2002
DOI: 10.1038/ncb785
|View full text |Cite
|
Sign up to set email alerts
|

E2F-dependent accumulation of hEmi1 regulates S phase entry by inhibiting APCCdh1

Abstract: Emi1 promotes mitotic entry in Xenopus laevis embryos by inhibiting the APC(Cdc20) ubiquitination complex to allow accumulation of cyclin B. We show here that human Emi1 (hEmi1) functions to promote cyclin A accumulation and S phase entry in somatic cells by inhibiting the APC(Cdh1) complex. At the G1-S transition, hEmi1 is transcriptionally induced by the E2F transcription factor, much like cyclin A. hEmi1 overexpression accelerates S phase entry and can override a G1 block caused by overexpression of Cdh1 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
376
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(405 citation statements)
references
References 48 publications
25
376
3
1
Order By: Relevance
“…More importantly, we further demonstrated that ectopic expression of cyclin E led to an increase in the phosphorylation of endogenous Cdh1 ( Figure 4H), whereas depletion of cyclin E resulted in a sharp decrease in endogenous Cdh1 phosphorylation ( Figure 4I). Therefore, consistent with previous reports [25,44,45], these results support a model that the Fbw7/cyclin E signaling pathway potentially regulates the E3 ligase activity of APC Cdh1 by affecting the interaction of Cdh1 with the APC core subunit primarily through regulating Cdh1 phosphorylation status ( Figure 6). …”
Section: Cdk2/cyclin E Directly Phosphorylates Cdh1 At Multiple Sitessupporting
confidence: 81%
“…More importantly, we further demonstrated that ectopic expression of cyclin E led to an increase in the phosphorylation of endogenous Cdh1 ( Figure 4H), whereas depletion of cyclin E resulted in a sharp decrease in endogenous Cdh1 phosphorylation ( Figure 4I). Therefore, consistent with previous reports [25,44,45], these results support a model that the Fbw7/cyclin E signaling pathway potentially regulates the E3 ligase activity of APC Cdh1 by affecting the interaction of Cdh1 with the APC core subunit primarily through regulating Cdh1 phosphorylation status ( Figure 6). …”
Section: Cdk2/cyclin E Directly Phosphorylates Cdh1 At Multiple Sitessupporting
confidence: 81%
“…Cdh1 is inhibited in all systems by cyclin-Cdk phosphorylation, and is also inhibited by stoichiometric-binding proteins (Emi1 and Acm1). In animals, Emi1 is an E2F transcriptional target, which binds and inhibits Cdh1 [48]; in yeast, Acm1 similarly binds and inhibits Cdh1 [49] and is expressed specifically at G1-S, probably under SBF control [50]. However, Acm1 and Emi1 lack detectable sequence similarity [51].…”
Section: The G1 -S Regulatory Network In Budding Yeast and Animals Hamentioning
confidence: 99%
“…It relies on Cdh1, the G 1 -phase-specific adaptor subunit (Wa¨sch et al, 2010), and goes hand in hand with marked decline of Emi1 expression, the main interphase inhibitor of the APC/C (Hsu et al, 2002). Importantly, activation of APC/C-Cdh1 is required for timely destruction of a broad range of APC/C substrates after DNA damage.…”
Section: Introductionmentioning
confidence: 99%